2020
DOI: 10.21203/rs.3.rs-105337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Prognostic Implications of an Immune-Related Risk Model Based on TP53 Status in Lung Adenocarcinoma

Abstract: Background: TP53 mutation is the most widespread mutation in lung adenocarcinoma (LUAD), meanwhile p53 (encoded by TP53) has recently been implicated in immune responses. However, it is still unknown whether TP53 mutation may remodel tumor microenvironment to influence tumor progression and prognosis in LUAD.Methods: we developed a six-gene immune-related model (IRM) to predict the survival of patients with LUAD in TCGA cohort based on TP53 status using LASSO Cox analysis, which was also confirmed the predicti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The genes included in the molecular typing of LUAD often include EGFR, ALK, ROS1, BRAF, NTRK1/2/3, MET, and RET, and the mutation rate of functional driver genes is about 60%, among which KRAS, EGFR mutations and EML4-ALK fusion is the most common driver gene, accounting for about 35% to 40% (23)(24)(25). The study by Jones et al showed that KRAS G12C mutation was associated with worse disease-free survival after complete resection of stage I-III LUAD (26).…”
Section: Discussionmentioning
confidence: 99%
“…The genes included in the molecular typing of LUAD often include EGFR, ALK, ROS1, BRAF, NTRK1/2/3, MET, and RET, and the mutation rate of functional driver genes is about 60%, among which KRAS, EGFR mutations and EML4-ALK fusion is the most common driver gene, accounting for about 35% to 40% (23)(24)(25). The study by Jones et al showed that KRAS G12C mutation was associated with worse disease-free survival after complete resection of stage I-III LUAD (26).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, abnormal p53 contributes to immune escape, resulting in an immunosuppressive microenvironment (55). It has been shown that TP53 mutation could lead to reduced immunity in LUAD patients (56). As a result, higher frequencies of TP53 mutation in patients in the CSFI-high group might have contributed to the immunosuppressed state of these patients.…”
Section: Discussionmentioning
confidence: 99%